Impact of the nonlinear thermal radiation on the Arrhenius activation energy of tangent hyperbolic micropolar hybrid nanofluid flow across an extending surface - MD. Shamshuddin; Balasani Srinitha; S.O. Salawu; M. Sunder Ram (Partial Differential Equations in Applied Mathematics)
Our study is built on a rigorous methodology, exploring the impact of hybridized nanofluids flow with magnetohydrodynamics and micropolar properties over a stretched sheet. The hybrid nanofluid, a unique blend of silver (Ag), and alumina (Al2O3) nanoparticles in water significantly enhance the thermal properties of conventional fluids. We investigate the system's thermal distribution by considering nonlinear heat radiation impacts and examine the system's mass transfer by studying Arrhenius's activation energy influences. The energy transmission and fluid flow are mathematically specified using a coupled nonlinear system of PDEs (partial derivative equations). The system of PDEs is transmuted into a dimensionless form of ODEs (ordinary derivative equations), which are then further treated with the MAPLE package based on the Runge-Kutta 4th order with shooting procedure. The influence of diverse terms on flow fields was examined via plotted graphs. We observed a significant reduction in liquid velocity and enhancement in angular momentum with the variations in amplitude of magnetic intensity. Two-fold behaviours are seen in the temperature profile for high radiation parameter estimates. Engineering quantities maximized for higher involvement of different parameters. Comparative analysis with existing work reveals both similarities and discrepancies, underscoring the complexity of micropolar hybrid nanofluid behaviour under assorted conditions.